1360Health impacts of a 4 month community-wide lockdown: a prospective longitudinal study in Victoria, Australia. (2nd September 2021) - Griffiths, Daniel; Sheehan, Luke; Vreden, Caryn van; Petrie, Dennis; Sim, Malcolm; Collie, Alex
Abstract: Background: In response to the second wave of COVID-19 in Australia a 4 month community-wide lockdown resulted in Victoria, Australia. We explored the health impacts during lockdown and following its conclusion. Methods: A cohort of 898 working-age Australians enrolled in a national longitudinal cohort study, completing surveys prior to, during, and following a Victorian lockdown during the southern hemisphere winter and early spring 2020. Mixed linear regression models examined health outcomes during and following the lockdown. Generalised estimating equations assessed changes in several determinants of health such as social interactions, engagement in work and finances. Results: The Victorian lockdown had negative consequences for mental health and increased levels of psychological distress. These health impacts coincided with greater social isolation and cessation of work. Following the conclusion of lockdown, outcomes assessing mental health, work and social interactions had recovered to an extent whereby no significant long-lasting effects were identified compared to pre-lockdown conditions. Conclusions: Extended community lockdowns have adverse health consequences. Governments should weigh the potential health impacts of lockdown with the benefits of reducing COVID-19 transmission. Services and programs to reduce the negative impacts of lockdown may include increases in mental health care, encouraging safe social interactions and financial support to maintain employment relationships. Longer-term follow-up is required to identify any persistent health effects of community lockdowns. Key messages: Lockdowns result in adverse health consequences, and some quickly recover. Timely services and programs are encouraged to reduce negative impacts of lockdowns such as mental health supports and promoting safe interactions.